Modeling of salt and gypsum dissolution: applications, evaluation of geomechanical hazards. Issue 8 (3rd July 2021) - Laouafa, Farid; Guo, Jianwei; Quintard, Michel
Abstract: This article addresses the problem of modeling the dissolution of cavities in gypsum and halite (salt), followed by the assessment of potential collapse or subsidence of the geological formation, which may induce damaging consequences for population and infrastructures. Hazard prediction relies mostly on numerical modeling. This article discusses several issues associated to the development of dissolution numerical models involving the coupling between transport, dissolution and geomechanical modeling: type of model, parameters and numerical strategies. Hazard prediction relies mostly on numerical modeling. This article discusses several issues associated to the development of dissolution numerical models involving the coupling between transport, dissolution and geomechanical modeling: type of model, parameters and numerical strategies. The methodology is illustrated on several boundary value problems typical of actual situations in mining or civil engineering.